Antiangiogenic effect of sambung nyawa leaves (Gynura procumbens (Lour.) Merr.) etanolic extract on chick embryo chorioallantoic membrane (CAM) - Riris Istighfari Jenie; Edy Meiyanto; Retno Murwanti (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2006)
Antiangiogenesis (inhibition of new blood vessels formation) has become a strategy to inhibit cancer development lack of nutrition and oxygen supply. The aim of the present research is to investigate antiangiogenesis effect of ethanolic extract of Gynura procumbens (Lour.) Merr. Leaves in situ using chick embryo chorioallantoic membrane (CAM). Eight to 9 days old fertilized chicken eggs were treated with b-FGF (angiogenesis inductor) and extracts. Eggs were then incubated for 3 days in order to observe its angiogenesis response (new blood vessels converged toward the implant).The results showed that the ethanolic extract of G.procumbens could inhibit angiogenesis in a dose-dependent manner. Doses 10, 20, 40, 80 ug gave angiogenesis response of (in percent) 82.32 ± 6.33; 68.38 ± 6.24; 56.48 ± 11.61; 41.43 ± 7.46 (p<0.05), respectively. These results indicate a potential antiangiogenic effect of the extract.Key words: antiangiogenic, CAM, G.procumbens.